Deformations of geosynthetic reinforced soil under bridge service loads. Issue 4 (August 2016) - Nicks, Jennifer E.; Esmaili, Danial; Adams, Michael T.
Abstract: This paper evaluates the results of 13 large scale Geosynthetic Reinforced Soil (GRS) column load tests, also known as performance tests (PT) or mini-pier tests, to study the effect of tensile strength (Tf ), vertical reinforcement spacing (Sv ), facing elements, and backfill properties on the deformations of GRS at 200 kPa, typical bridge bearing pressures, and also at 400 kPa. The results indicate that GRS performs well under service conditions. A semi-empirical expression is proposed for prescribed bearing pressures to limit vertical strain to 0.5% of the abutment height. In addition, recommendations for estimating lateral deformation for GRS bridge abutments are also provided. At 200 kPa surcharge for this series of tests, vertical settlements ranged from 8.3 to 33.9 mm (or from 0.4% to 1.7% axial strain); lateral deformations ranged from 3.0 mm to 10.1 mm (or 0.6%–2.0% lateral strain); and reinforcement strain ranged from less than 1% during construction to less than 3% during loading. The lateral deformation results indicate that the maximum displacement occurs in the top third region of the wall face. Comparing the vertical and lateral displacement data shows that most GRS models experienced negligible positive volume changes up to about 1% under typical bridge service loads.